Functional condition of the endothelium in men with primary gout and initial signs of renal dysfunction - Daniuk, I. O.; Dotsenko, S. Ya.; Rekalov, D. H. (Zaporozhye Medical Journal, 2019)
Background. Among the causes of mortality in patients with gout, cardiovascular complications and chronic renal failure are prevailed. The searching for the markers of the initial signs of endothelial and renal dysfunction is relevant for the early diagnosis of target organs damage. Objective. To determine the indicators of endothelial dysfunction in men with primary gout with normal glomerular filtration rate (GFR) and men with stage 1 chronic renal failure (CRF). Materials and methods. 30 men with primary gout and GFR > 90 ml / min, 30 men with primary gout and GFR = 89–60 ml / min and 30 healthy men were examined. We determined the concentration of endothelin-1 (ET-1), vascular cell adhesion molecule-1 (VCAM-1), total nitric oxide metabolites (NO), serum cystatin C, level of albuminuria and endothelium-dependent vasodilatation (EDVD). Results. An increase in NO, ET-1, VCAM-1, cystatin C and normal values of EDVD and albuminuria were found in men with primary gout and normal GFR in comparison to the control. In patients with gout and CRF (stage 1), a significant increase in ET-1, VCAM-1, cystatin C, albuminuria and a decrease in NO and EDVD were detected compared to the men with primary gout and GFR >90 ml / min. Conclusions. Patients with primary gout and normal GFR are characterized by NO hyperproduction providing the vasomotor endothelial function preservation. An increase in the level of cystatin C in these patients compared to the healthy men indicates the beginning of renal filtration function deterioration. Patients with gout and CRF (stage 1) are characterized by significant impairment of vasomotor endothelial function, an increased synthesis of pro-inflammatory markers and a decreased NO production.